Mumps in Patients with Acute Encephalitis Syndrome in Assam, India during January 2018 to July 2021 - Kimmi Sarmah; Kishore Sarma; Prasanta Kumar Borah; Ajanta Sharma; Jagadish Mahanta; Biswajyoti Borkakoty (Indian Journal of Public Health)
Acute encephalitis syndrome (AES), a major public health problem, has been reported worldwide. The potential etiology of AES varies from viruses, bacteria, fungi, and parasites with viruses being most prevalent. The virus-mediated AES in Assam is not well characterized. Most viruses causing AES lack specific treatment, but encephalitis caused by mumps virus (MuV) can be effectively treated. Therefore, the present study was undertaken to identify MuV positivity in AES cases during January 2018–July 2021. Using enzyme immunoassay MuV immunoglobulin M antibodies were tested in 317 samples (cerebrospinal fluid and serum) of which positivity was found in 22.0% (70/317), with higher prevalence in males and bulk of cases occurring in July. Quantitative reverse transcription-polymerase chain reaction positive MuV cases were genotyped targeting small hydrophobic gene which revealed the circulation of genotypes C and G during the studied period. Despite Japanese encephalitis (JE) being considered the major viral etiology for AES, the present study highlights the emergence of MuV over JE with time.